The Role of Digital Technologies in Creating Competitive Advantages of Modern Entrepreneurship - PROKHORUK, Roman; ULINICI, Andrian; VASYLYNA, Orysia; BILOUS, Anastasiia; GRECHAN, Alla (Theoretical and Practical Research in Economic Fields, 2025)
Digital technologies have become a key factor in transforming entrepreneurship and strengthening its competitiveness in the current global instability and growing competition. Digitalization is especially important for countries that are undergoing post-crisis recovery and integration into the European space, where it forms new mechanisms for economic growth, opens access to new markets, and optimizes business processes. The aim of this article is to assess the impact of digital technologies on the creation of competitive advantages of enterprises in Moldova, Romania, Ukraine, Poland, and Germany using an econometric approach. The research methodology is based on a panel data model for 2019–2024 considering fixed effects. The model includes five independent variables: the level of digitalization, the number of innovations, the share of R&D spending, export orientation, and enterprise size. The modelling results showed that R&D has the strongest positive impact (β=8.70), followed by digitalization (β=0.52), and innovation (β=0.31). The highest average competitiveness was recorded in Germany (3.62), the lowest - in Poland (3.27), while Ukraine has a consistently positive dynamic. The developed model confirms the importance of comprehensive digital transformation for ensuring long-term market advantage. Further studies may expand the model, considering industry specifics, digital environmental friendliness, sustainability, and regional characteristics of the countries of Central Asia, the Balkans, and the Baltics.